Self-Love in Religious Altruism: A Dialogical Comparison between Thomas Aquinas and Śāntideva - Rouyan, Gu (Buddhist Christian studies, 2026)
The theme of altruism is a central concern in Christian and Buddhist ethics. As far as religious altruism is concerned, a devotion to selflessness constitutes the most significant similarity between the two religions. The role of self-love in Christian and Buddhist articulations of altruism, on the other hand, remains an understudied issue. This article capitalizes on this research gap to rethink religious altruism. Offering a dialogical comparison between Thomas Aquinas and Śāntideva, this article argues that self-love is an essential aspect in understanding religious altruism.